2008
DOI: 10.1093/scan/nsn040
|View full text |Cite
|
Sign up to set email alerts
|

A neural basis for the effect of candidate appearance on election outcomes

Abstract: Election outcomes correlate with judgments based on a candidate's visual appearance, suggesting that the attributions viewers make based on appearance, so-called thin-slice judgments, influence voting. Yet, it is not known whether the effect of appearance on voting is more strongly influenced by positive or negative attributions, nor which neural mechanisms subserve this effect. We conducted two independent brain imaging studies to address this question. In Study 1, images of losing candidates elicited greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 41 publications
4
62
0
Order By: Relevance
“…Research has begun to investigate neural activation that underlies the processing of political attitudes and preferences (Amodio et al, 2007;Zamboni et al, 2009), including studies on deliberative processing of political statements and simulated voting for political candidates (Westen et al, 2006;Spezio et al, 2008;Gozzi et al, 2010;Bruneau and Saxe, 2010;Rule et al, 2010).Yet the neural substrate underlying automatic processing of political preferences (Todorov et al, 2005;Ballew and Todorov, 2007;Berger et al, 2008;Galdi et al, 2008;Hassin et al, 2007;Carter et al, 2011;Healy et al, 2010) remains largely unstudied. Extending earlier fMRI studies, the present studyshowed that brain responses can reflect individual political preferences -for politicians and associated parties -in the absence of conscious deliberation and attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has begun to investigate neural activation that underlies the processing of political attitudes and preferences (Amodio et al, 2007;Zamboni et al, 2009), including studies on deliberative processing of political statements and simulated voting for political candidates (Westen et al, 2006;Spezio et al, 2008;Gozzi et al, 2010;Bruneau and Saxe, 2010;Rule et al, 2010).Yet the neural substrate underlying automatic processing of political preferences (Todorov et al, 2005;Ballew and Todorov, 2007;Berger et al, 2008;Galdi et al, 2008;Hassin et al, 2007;Carter et al, 2011;Healy et al, 2010) remains largely unstudied. Extending earlier fMRI studies, the present studyshowed that brain responses can reflect individual political preferences -for politicians and associated parties -in the absence of conscious deliberation and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of a multiplechoice questionnaire of party affiliations showed that facial appearance of unfamiliar politicians did not allow identification of the associated political party above chance. Face-specific ratings obtained in pretest 2 also allowed selection of stimuli that were matched across experimental conditions with respect to judgments of facial attractiveness, trait inferences such as trustworthiness, competence, and threat, as well as valuation ratings for politicians ( Figure 1A) (Winston et al, 2002;Todorov et al, 2005;Engell et al, 2007;O'Doherty et al, 2003;Spezio et al, 2008;van 't Wout and Sanfey, 2008). Please note that similar face-specific ratings were collected for participants subsequent to scanning to validate the results of the behavioral pretests.…”
Section: Stimulimentioning
confidence: 98%
See 1 more Smart Citation
“…This ranges from assessment of traits that are related directly to appearance, such as attractiveness (Thornhill and Gangestad, 1999;O'Doherty et al, 2003;, to inferences about personal characteristics, such as intelligence, warmth, or neuroticism (Berry, 1989;Zebrowitz et al, 2002;Bar et al, 2006;Penton-Voak et al, 2006;Little and Perrett, 2007). Although inferences based on appearance can be inaccurate (Olivola and Todorov, 2010), first impressions nonetheless can strongly influence social decision-making (Hassin and Trope, 2000;Bhanji and Beer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been linked to the assessment of social information from photographs or videos (O'Doherty et al, 2003;Willis et al, 2010;Tsuchida and Fellows, 2012;Bhanji and Beer, 2013), including the judgment of beauty (or esthetic value) in faces (Pegors et al, 2015).…”
Section: Introductionmentioning
confidence: 99%